2002
DOI: 10.1080/20028091057466
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Sediment Quality Weight-of-Evidence (WOE) Assessments

Abstract: Uncertainties in sediment quality assessments are discussed in five categories: (1) sediment sampling, transport and storage; (2) sediment chemistry; (3) ecotoxicology; (4) benthic community structure; and (5) data uncertainties and QA/QC. Three major exposure routes are considered: whole sediments, and waters in sediment pores and at the sediment-water interface. If these uncertainties are not recognized and addressed in the assessment process, then erroneous conclusions may result. Recommendations are provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 118 publications
(92 reference statements)
0
30
0
3
Order By: Relevance
“…Assessments conducted with these databases in conjunction with field validation studies involving contaminated sediments suggest that SQGs are reasonable predictors primarily of acute effects or no effects on benthic organisms. However, several limitations have been observed regarding the use of SQGs in sediment quality assessments [10,11]. One concern is the capability of SQGs to predict adequately the presence or absence of chronic toxicity to sediment-dwelling organisms in field-collected sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Assessments conducted with these databases in conjunction with field validation studies involving contaminated sediments suggest that SQGs are reasonable predictors primarily of acute effects or no effects on benthic organisms. However, several limitations have been observed regarding the use of SQGs in sediment quality assessments [10,11]. One concern is the capability of SQGs to predict adequately the presence or absence of chronic toxicity to sediment-dwelling organisms in field-collected sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated that defaunated sediments sourced from locations with high trace metal concentrations were colonised by different faunal assemblages to sediments sourced from a location with lower concentrations. While no single approach can provide a confident and robust assessment of the ecological status of a location, when coupled with field surveys and/or toxicological data, manipulative translocation experiments provide an additional line of ecological information which can be integrated into a weight-of-evidence approach for assessing the risks associated with contaminated sediments (Batley et al 2002). The translocation technique used in this experiment is simpler and more accurate than spiking with a complex mixture of contaminants, and incorporates other chemicals which may not have been foreseen.…”
Section: Discussionmentioning
confidence: 99%
“…As benthic communities are continually modified by numerous abiotic and biotic processes, the correlative models that underpin many of these studies (survey and gradient) do not permit a direct link to causality (Luoma 1996). The influences of natural variability, sampling error, and additional (often unidentified) contaminants can also confound the findings of survey studies, reducing our ability to confidently identify and assess the ecological risks associated with a particular location (Suter and Barnthouse 1993; Batley et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…However, sediment guidelines and their derivation methods are still controversial, and their appropriateness should be carefully evaluated in terms of site management goals, study questions, and the CSM. Two recent documents that address the use of SQGs and weight-of-evidence frameworks are Chapman et al (2001) and Batley et al (2002). A recent Pellston workshop addressed this issue.…”
Section: Sediment Quality Guidelinesmentioning
confidence: 99%